Johnson, Rasselas, and the Choice of Criticism. - Tomarken, Edward, 1938- (The University Press of Kentucky, 1989)
Although Rasselas has received more critical commentary than almost any other work by Samuel Johnson, Edward Tomarken's book is the first full length study to focus on his tale of the Prince of Abyssinia. This anomaly arises, as Tomarken shows, because Rasselas has remained resistant to the customary critical approaches of the eighteenth, nineteenth, and twentieth centuries, consistently eliciting new kinds of insights and raising new sorts of problems. Tomarken' s contribution is a new methodology to explain this phenomenon. He sees Johnson's early writings, London and Irene, as instances o.